OPERASIE SAVANNAH DAGBOEK VAN KAPT J.A. LAUBSCHER - Du Preez, Sophia (Scientia Militaria - South African Journal of Military Studies, 2012)
The diary of Captain, as he was then, J.A. Laubscher forms the basis of this article. Since the ending of the SADF involvement in Angola, a number of books have been published concerning this conflict. This personal, day by day, account of events as they took place during Operation Savannah, is another chapter in the annals of South African military history.